Determinants of readmission amongst hospitalized patients with heart failure in Ghana and Nigeria: a prospective cohort study - Dzifa Ahadzi; Amudalat Issa; Odalys Rivera Hernandez; Olutobi Adekunle Sanuade; Mohammed Baba Abdulkadir; Ernest Yorke; Bamidele Tayo (BMC Cardiovascular Disorders)
Abstract Background Readmission following hospitalization for acute heart failure (HF) is an adverse prognostic event. Readmission rates for HF in African countries are variable, ranging from 1.53 to 25% in the first 30 days, and 12.2% to over 50% at 180 days. Few studies done in the African region have identified several determinants of HF readmission including New York Heart Association functional class, heart failure phenotype, older age, amongst others. This study sought to explore determinants of readmission amongst a contemporary cohort of adult patients hospitalized with HF in Ghana and Nigeria. Methods This was a multicenter prospective cohort study, with 30- and 90-day follow-up after recruitment, conducted from June 2021 to April 2022, in two tertiary teaching hospitals in Ghana and Nigeria. A total of 201 adult patients who presented with acute heart failure at the two study sites were consecutively enrolled. Results In this cohort of 201 patients (mean age (SD) 58.8 (15.6) years, 44.3% women), 8.0% and 13.9% were readmitted at 30- and 90-days, respectively. The odds of readmission at 30-days were higher in participants from Nigeria (OR = 4.3, 95% CI – 0.02–0.75, p = 0.039) and those with duration of heart failure diagnosis of 1 month to < 1 year (sub-acute HF) (OR = 4.0, 95% CI – -0.00-0.27, p = 0.045). Every unit increase in pulse rate was associated with almost 5-fold higher odds of readmission at 30-days (OR = 4.7, 95% CI – 0.00-0.01, p = 0.031). The odds of 90-day readmission were higher in participants with New York Heart Association functional class III-IV at discharge (OR = 5.1, 95% CI – -0.03–0.42, p = 0.025). Conclusion Heart failure patients with sub-acute HF, higher pulse rates at baseline and higher NYHA functional class at discharge, may represent a vulnerable group at high risk of readmission in Ghana and Nigeria. Future studies should explore the mechanisms underlying this observation and consider interventions to reduce the risk of readmission amongst this unique patient population. Clinical trial number Not applicable.